Study of Risk Factors for Stunting Incidents in Children Under Five in The Highlands and Lowlands of Pidie Regency - Rika Dewi; Putri Ilham Sari (Postgraduate, University of Mataram, 2025)
Stunting has been a prevalent health issue in Indonesia, and Aceh Province is not exempt from this challenge. This situation has placed a substantial responsibility on all stakeholders to collaboratively work towards reducing stunting cases in Aceh. This study aimed to investigate the risk factors associated with stunting in both the highland and lowland areas of Pidie Regency. This study employed an analytical observational design with a cross-sectional approach. The instrument used was a questionnaire, a total sampling technique was applied to survey 30 mothers with children under 2 years old in Tangse Sub-district and other 30 mothers in Mutiara Sub-district. In the highlands, specifically Tangse Sub-district, four predictors were identified as significant contributors to stunting, namely socio-economics (p value: 0.013), parents’ educational background (p value: 0.036), pregnancy checks (p value: 0.005), and nutritional intake (p value: 0.011). On the other hand, in a lowland area, in Mutiara Sub-district, additionally, parenting patterns (p value: 0.002) and exclusive breastfeeding (p value: 0.001) were identified as two other significant predictors of stunting in this region.The analysis leads to the conclusion that stunting prevalence was higher in the highlands of Tangse Sub-district (60%) compared to in the lowlands of Mutiara Sub-district(20%).